2009
DOI: 10.1590/s1677-55382009000500011
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for urinary and fecal incontinence in brazilian women

Abstract: Objective: To evaluate prevalence and risk factors of fecal and urinary incontinence (UI) in Brazilian women. Materials and Methods: 685 women older than 20 years of age answered a questionnaire about urinary and fecal symptoms, clinical and obstetric antecedents. They were grouped according to presence or absence of UI. Results: Urinary and fecal incontinence was reported in 27% and 2% of cases, respectively. Mean age of incontinent women was significantly higher than continent ones. Incontinent women had a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 20 publications
1
24
0
8
Order By: Relevance
“…In our study, the mean body mass index (BMI) was indicative of overweight, and the average number of pregnancies per woman (four pregnancies) are close to the results of Amaro et al (25). The latter analyzed the prevalence of and risk factors for UI, and found higher BMI in a group of incontinent women, when compared to a group of women without urinary leakage who had an average of 3.6 pregnancies.…”
Section: Scoressupporting
confidence: 89%
“…In our study, the mean body mass index (BMI) was indicative of overweight, and the average number of pregnancies per woman (four pregnancies) are close to the results of Amaro et al (25). The latter analyzed the prevalence of and risk factors for UI, and found higher BMI in a group of incontinent women, when compared to a group of women without urinary leakage who had an average of 3.6 pregnancies.…”
Section: Scoressupporting
confidence: 89%
“…No Brasil, trabalhos realizados tanto em populações específicas, como indígenas e mulheres na pós-menopausa, quanto naqueles feitos na comunidade, também mostram prevalências semelhantes às dos estudos internacionais [5][6][7][8]14 . No entanto, na amostra estudada, constituída por mulheres da comunidade, a prevalência de incontinência anal foi mais elevada.…”
Section: Discussionunclassified
“…Estudos realizados em populações brasileiras mostram prevalências díspares, variando entre 0,2 e 15%. A prevalência de IF numa população feminina de indígenas do Parque Nacional do Xingu foi de 0,2 % 5 , ao passo que mulheres no estado de São Paulo apresentaram taxa de 2 % 6 , sendo que todas as pacientes apresentavam simultaneamente IU. Já um estudo de base populacional realizado em Minas Gerais 7 , em indivíduos com mais de 18 anos, encontrou prevalência de 4,2 % para perda de fezes, de 4 % para perda de gases e de 7 % para a associação de ambas.…”
Section: Introductionunclassified
“…Urinary incontinence could harm women's emotional state, which will cause lower self-esteem and fear of sexual intercourse. 1 In a study, it was stated that urinary incontinence, Alzheimer's disease and stroke were the three chronic diseases that would badly affect and decrease the quality of health. 2 World Health Organization (WHO) stated that urinary incontinence was a major health problem, and there were more than 200 million populations in the world having problems with micturition.…”
Section: Discussionmentioning
confidence: 99%
“…12 However, it was still questioned whether caesarean section could prevent pelvic floor trauma. 1,[13][14][15] In a study, it was reported that women with persistent stress urinary incontinence at three months postpartum, 92% would continue to stress urinary incontinence for five years postpartum. [16][17][18] This study aimed to know the prevalence and risk factors of postpartum stress urinary incontinence (SUI) in Indonesia.…”
Section: Discussionmentioning
confidence: 99%